THE TIMING SCALE OF THE STEEP-SPECTRUM SOURCES - Miroshnichenko, A. P. (Одеські астрономічні публікації, 2013)
We continue to study the properties of the steep-spectrum sources from the Grakovo catalogue received with the radio telescope UTR-2. At this paper the lifetimes of steep-spectrum sources have been estimated. We have used two methods to determine the characteristic ages of the steep-spectrum galaxies and quasars: 1) at independent estimate of the source’s magnetic field strength; 2) at well-known condition of the equipartition of the magnetic field energy and the energy of the relativ- istic particles in objects. The derived alternative estimates of the characteristic age of steep-spectrum sources have been compared. The relations of ages and some physical parameters of the examined objects have been considered. The values of the source’s lifetime and the characteristic age indicate on the possibility of the activity recurrence of galaxies and quasars with steep radio spectrum.